Impact of Leadership Styles on Employees' Performance - Setiawan, I Gede Andri; nurtrisnawati; Sheidu, Comfort Fatimoh (SMARTINDO, 2024)
Purpose – This research is to determine the effect of leadership on employee performance. Methodology – This research uses qualitative methods and a literature review (Library Research) using an inductive analysis model. Researchers take library sources through online media on the Google Scholar application with the keyword